ANALISIS SWOT DALAM STRATEGI PEMASARAN PEMBIAYAAN SYARIAH PADA UNIT PENGELOLA KEGIATAN DI KECAMATAN SELAKAU KABUPATEN SAMBAS - Eko Wira Yhuda (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2023)
ABSTRACT: SWOT Analysis in the Marketing Strategy of Islamic Finance in the Activity Management Unit of Selakau District, Sambas Regency. Final project, 2022. This study aims to find out what strategies are used by the Selakau District Activity Management Unit in increasing marketing of sharia financing. While this research method uses qualitative methods, with a sample of 9 informants from Selakau District Activity Management Unit employees. By using a questionnaire the questions posed to UPK Selakau District employees. The analysis used is swot analysis to determine the strength of the strategy used. The results of this study indicate that, with a sample of 9 informants from UPK employees in Selakau District, data from the SWOT analysis shows that there are several strengths, weaknesses, opportunities and threats, including: strengths possessed, do not use conventional interest, using a profit-sharing system and the existence of buildings. Weaknesses, limited funding, many are still in arrears and limited funding. Opportunities, technological advances and women-only business groups. Threats, the impact of the covid-19 pandemic, limited capital and unhealthy economic conditions. The strategy used by the Selakau District activity management unit is to distribute loan information brochures to the community, offer products with a profit-sharing system, conduct outreach to villages in Selakau District, approach online and take a family approach. limited capital and unhealthy economic conditions. The strategies used by the Selakau District activity management unit are distributing loan information brochures to the community, offering products with a profit-sharing system, conducting socialization to villages in Selakau District, online approaches and taking a family approach. limited capital and unhealthy economic conditions. The strategies used by the Selakau District activity management unit are distributing loan information brochures to the community, offering products with a profit-sharing system, conducting socialization to villages in Selakau District, online approaches and taking a family approach.